Activating transcription factor 6α deficiency exacerbates oligodendrocyte death and myelin damage in immune‐mediated demyelinating diseases. Issue 7 (13th February 2018) - Stone, Sarrabeth; Wu, Shuangchan; Jamison, Stephanie; Durose, Wilaiwan; Pallais, Jean Pierre; Lin, Wensheng
Abstract: Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) play a critical role in immune‐mediated demyelinating diseases, including multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE), by regulating the viability of oligodendrocytes. Our previous studies show that activation of the PERK branch of the UPR protects myelinating oligodendrocytes against ER stress in young, developing mice that express IFN‐γ, a key pro‐inflammatory cytokine in MS and EAE, in the CNS. Several studies also demonstrate that PERK activation preserves oligodendrocyte viability and function, protecting mice against EAE. While evidence suggests activation of the ATF6α branch of the UPR in oligodendrocytes under normal and disease conditions, the effects of ATF6α activation on oligodendrocytes in immune‐mediated demyelinating diseases remain unknown. Herein, we showed that ATF6α deficiency had no effect on oligodendrocytes under normal conditions. Interestingly, we showed that ATF6α deficiency exacerbated ER stressed‐induced myelinating oligodendrocyte death and subsequent myelin loss in the developing CNS of IFN‐γ‐expressing mice. Moreover, we found that ATF6α deficiency increased EAE severity and aggravated EAE‐induced oligodendrocyte loss and demyelination, without affecting inflammation. Thus, these data suggest the protective effects of ATF6α activation on oligodendrocytes in immune‐mediated demyelinating diseases. Main Points: ATF6α deficiency exacerbates ER stressed‐induced oligodendrocyte death in the developing CNS of IFN‐γ‐expressing mice. ATF6α deficiency exacerbates EAE severity and EAE‐induced oligodendrocyte loss and myelin loss, without affecting inflammation.